Examining a new automobile global manufacturing system - Amasaka, Kakuro, 1947- (Advances in logistics, operations, and management science (ALOMS) book series., 2022)
"In this book, the author predicts the form of next generation automobile manufacturing, presenting a "New Automobile Global Manufacturing System" (NAGMS) that contains the hardware system with five core elements - "TDS, TPS, TMS, TIS and TJS" (Total Development System, Total Production System, Total Marketing System, Total Intelligence Management System and Total Job Quality Management System) for transforming management technology into automobile management strategy-Surpassing JIT"--